Global structure of ionospheric TEC anomalies driven by geomagnetic storms. (July 2016) - Pancheva, D.; Mukhtarov, P.; Andonov, B.
Abstract: This study examines the structure and variability of the ionospheric TEC anomalies driven by geomagnetic storms. For this purpose the CODE global ionospheric TEC data from four geomagnetically disturbed periods (29 October–1 November 2003, 7–10 November 2004, 14–15 December 2006, and 5–6 August 2011) have been considered. By applying the tidal analysis to the geomagnetically forced TEC anomalies we made an attempt to identify the tidal or stationary planetary wave (SPW) signatures that may contribute to the generation of these anomalies. It has been found that three types of positive anomalies with different origin and different latitudinal appearance are observed. These are: (i) anomalies located near latitudes of ±40° and related to the enhancement and poleward moving of the equatorial ionization anomaly (EIA) crests; (ii) anomalies located near latitudes of ±60° and seen predominantly in the night-side ionosphere, and (iii) very high latitude anomalies having mainly zonally symmetric structure and related to the auroral heating and thermospheric expansion. The decomposition analysis revealed that these anomalies can be reconstructed as a result of superposition of the following components: zonal mean (ZM), diurnal migrating (DW1), zonally symmetric diurnal (D0), and stationary planetary wave 1 (SPW1). Highlights: Global structure of the positive ionospheric TEC anomalies driven by geomagnetic storms is defined. Three types of positive anomalies with different origin and different latitudinal appearance are found. Tidal/zonal wave signatures contributing to these anomalies are identified and quantify by tidal analysis.